Pengaruh Pengetahuan Terhadap Perilaku Penerapan Protokol Kesehatan Saat Pandemi Covid-19 Pada Remaja - Widayanti, Linda Prasetyaning (Jurnal Surya, 2021)
Background: Covid-19 pandemic now at its second year. Covid-19 can be transmitted from infected droplets. New variants of Covid-19 began to appear due to genetic mutations in several countries. There is no medicine that can cure Covid-19. Only vaccinations and compliance with health protocols are the hope to eliminate Covid-19 pandemic. Wear masks, wash hands, keep distance, stay away from crowds and minimize mobility. The number of confirmed cases in Indonesia reached more than two million in June 2021 and 2-4% were teenagers. Teenagers during the pandemic are asked to comply with health protocols. Obedient behavior is driven by adequate knowledge.Objectives: This study purpose was to analyze the effect of knowledge on the behavior of implementing health protocols in adolescents.Design: This research was a quantitative with an analytical observational design. Based on the time of data collection, this study was a cross-sectional design. The independent variable was knowledge while the dependent variable was behavior. Data was analyzed by logistic regression.Data Sources: Data was collected with questionnaire distributed by google form application.Results: The results of this study were most of respondents were less than 20 years old, female and obtained information about Covid-19 from the internet. Most of the respondents had good knowledge and behavior of Covid-19 health protocols. The results of the logistic regression test showed p value = 0.014 <0.05 where H0 was rejected. OR value = 2.1551.Conclusions: There was a significant effect of knowledge on behavior of Covid-19 health protocol.